SEJARAH PERTANGGUNGJAWABAN PIDANA BENEFICIAL OWNER DI INDONESIA - H, Dicky J (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2020)
The history of the criminal liability of  Beneficial Owner in the World is very  influenced by the UK and the United States where in tax treaties and international organizations such as the FATF, AEOI, OECD which often use the term beneficial owner, become the basis for the development of the beneficial owner concept in the World. The history of corporate regulation as a subject of criminal law in Indonesia consists of two periods, namely the KUHP period (before the existence of laws outside the KUHP) and a period outside the KUHP (the birth of new laws that specifically regulate corporations as legal subjects, such as Law No. 7 Drt. 1955 concerning Investigation, Prosecution, Economic Crime Court, Law No. 41 of 1999 concerning Forestry, Law No. 32 of 2009 concerning Protection and Management of the Environment, Law No. 8 of 2010 concerning Prevention and Eradication of Money Laundering and Law No. 20 of 2001 on the Second Amendment to Law No. 31 of 1999 on Corruption.